2021
DOI: 10.3390/agriculture11121293
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Pyrolytic Temperature, Particle Size, and Application Rate of Biochar in Improving Hydro-Physical Properties of Calcareous Sandy Soil

Abstract: Water management and irrigation conservation in calcareous sandy soil are of significant importance for sustaining agricultural production, especially in arid and semi-arid region that facing scarcity of water resources. The changes in hydro-physical characteristics of calcareous sand soil were investigated after date palm waste-derived biochar application in column trials. Significance of pyrolysis temperature (300 °C, 500 °C, and 700 °C), particle size [<0.5 mm (D0.5), 0.5–1 mm (D1), and 1–2 mm (D2)], and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Our locally produced biochar is a mixture of different particle sizes ( Table 1 ) which positively affects porosity at all levels, including micropores, mesopores, and macropores. The variety of biochar particle sizes is beneficial for improving soil porosity, as discovered by Alghamdi et al [ 39 ], who identified a correlation between the size of biochar particle size and its impact on soil pores. Liu et al [ 40 ] also reported that each pore size specifically affects soil water retention.…”
Section: Discussionmentioning
confidence: 99%
“…Our locally produced biochar is a mixture of different particle sizes ( Table 1 ) which positively affects porosity at all levels, including micropores, mesopores, and macropores. The variety of biochar particle sizes is beneficial for improving soil porosity, as discovered by Alghamdi et al [ 39 ], who identified a correlation between the size of biochar particle size and its impact on soil pores. Liu et al [ 40 ] also reported that each pore size specifically affects soil water retention.…”
Section: Discussionmentioning
confidence: 99%
“…These enhancements improve soil quality, increase water use efficiency, and reduce water stress on crop yields. Alghamdi et al 4 , 5 reported a significant decrease in soil-saturated hydraulic conductivity for all treatments compared to control after adding biochar produced at different pyrolysis temperatures and application rates.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, to maximize agricultural production, scientists search for amendments that can improve the hydro-physical properties of these soils. Biochar produced from organic wastes pyrolysis has been used as a soil amendment to ameliorate soil physicochemical and hydrological properties 3 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Practices which could decrease the amount of irrigation water, without reducing yield, are required, especially in arid environments [3,5]. Therefore, the partial root zone drying (PRD) method, regulated deficit irrigation (RDI), and the addition of soil conditioners, such as biochar, are considered important approaches that can conserve irrigation water and increase yields and water productivity (WP) [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Tomato, green bean, safflower, and eggplant have Ky values equal to 0.99, 1.23, 0.97, and 1.37, respectively [17,19,21,22]. Alghamdi et al [6] stated that the application of biochar with suitable application rates could improve the hydro-physical properties of soil in arid conditions.…”
Section: Introductionmentioning
confidence: 99%